Comparisons of stress-related neuronal activation induced by restraint in adult male rat offspring with prenatal exposure to buprenorphine, methadone, or morphine - Chia-Yen Wu; Hwei-Hsien Chen; Pao-Luh Tao; Zung Fan Yuan (Chinese Journal of Physiology, 2023)
Prenatal opioid exposure may impede the development of adaptive responses to environmental stimuli by altering the stress-sensitive brain circuitry located at the paraventricular nucleus of the hypothalamus (PVH) and locus coeruleus (LC). Corticotropin-releasing factor (CRF) released from neurons in the PVH has emerged as a key molecule to initiate and integrate the stress response. Methadone (Meth) and buprenorphine (Bu) are two major types of synthetic opioid agonists for first-line medication-assisted treatment of opioid (e.g., morphine, Mor) use disorder in pregnant women. No studies have compared the detrimental effects of prenatal exposure to Meth versus Bu on the stress response of their offspring upon reaching adulthood. In this study, we aimed to compare stress-related neuronal activation in the PVH and LC induced by restraint (RST) stress in adult male rat offspring with prenatal exposure to the vehicle (Veh), Bu, Meth, or Mor. CFos-immunoreactive cells were used as an indicator for neuronal activation. We found that RST induced less neuronal activation in the Meth or Mor exposure groups compared with that in the Bu or Veh groups; no significant difference was detected between the Bu and Veh exposure groups. RST-induced neuronal activation was completely prevented by central administration of a CRF receptor antagonist (α-helical CRF9-41, 10 μg/3 μL) in all exposure groups, suggesting the crucial role of CRF in this stress response. In offspring without RST, central administration of CRF (0.5 μg/3 μL)-induced neuronal activation in the PVH and LC. CRF-induced neuronal activation was lessened in the Meth or Mor exposure groups compared with that in the Bu or Veh groups; no significant difference was detected between the Bu and Veh exposure groups. Moreover, RST- or CRF-induced neuronal activation in the Meth exposure group was comparable with that in the Mor exposure group. Further immunohistochemical analysis revealed that the Meth and Mor exposure groups displayed less CRF neurons in the PVH of offspring with or without RST compared with the Bu or Veh groups. Thus, stress-induced neuronal activation in the PVH and LC was well preserved in adult male rat offspring with prenatal exposure to Bu, but it was substantially lessened in those with prenatal exposure to Meth or Mor. Lowered neuronal activation found in the Meth or Mor exposure groups may be, at least in part, due to the reduction in the density of CRF neurons in the PVH.